Flexible Working Arrangements, Job Satisfaction, and Employee Performance in Public Sector - Dewantoro Dewantoro; Anita Maharani; Endi Rekarti (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2026)
Aim: This study examines the effect of Flexible Working Arrangement (FWA) on employee performance with job satisfaction as a mediating variable among civil servants at PUSINTEK, Ministry of Finance of the Republic of Indonesia. Method: A quantitative survey design was employed, collecting data from 100 civil servants through structured questionnaires using a five-point Likert scale. The study measured five constructs comprising 30 indicators: FWA, job satisfaction, employee performance, technological support, and bureaucratic work culture. Data were analysed using Structural Equation Modelling–Partial Least Squares (SEM-PLS) via SmartPLS 4 software. Results: FWA exerted a significant positive effect on job satisfaction (β = 0.667, p < 0.001) and directly on employee performance (β = 0.323, p = 0.010). Job satisfaction significantly mediated the FWA–performance relationship (partial mediation), while technological support and bureaucratic work culture did not yield significant moderating effects. Novelty: This study is among the first to empirically examine FWA in an Indonesian central government institution undergoing digital bureaucratic transformation, establishing job satisfaction as a psychological mediating mechanism and revealing that structural/contextual moderators are less influential than motivational factors in technology-driven public organisations.